Genome-wide identification, characterization, and expression analysis of BZR transcription factor family in Gerbera hybrida - Qishan Luo; Gan Huang; Xiaohui Lin; Xiaojing Wang; Yaqin Wang (BMC Plant Biology)
Abstract Background The BZR family genes encode plant-specific transcription factors as pivotal regulators of plant BR signaling pathways, critically influencing plant growth and development. Results In this study, we performed a genome-wide investigation of the BZR family gene in gerbera to identify the key components of the BR pathway that may function in petal growth. The identified BZR genes, named GhBEH1-7 (GhBEH1, GhBEH2, GhBEH3, GhBEH4, GhBEH5, GhBEH6, GhBEH7), are distributed across chromosomes 3, 5, 10, 11, 12, 14 and 15. These genes exhibit similar exon–intron structures and possess typical BZR family structures. Phylogenetic analysis clustered these genes into two distinct subgroups. Analysis of cis-acting elements revealed their involvement in hormone response, stress response, and growth regulation. Subcellular localization analysis indicated nuclear localization for GhBEH1 and GhBEH2, while the remaining five genes exhibited dual localization in the nucleus and cytoplasm. The transactivation assay indicated that GhBEH1 and GhBEH2 may function as transcriptional repressors, contrasting with the transcriptional activation observed for the other five genes. Notably, seven GhBEHs exhibit various expression patterns under different growth stages of ray florets and BR treatment conditions. Meanwhile GhBEH1 and GhBEH2 showed pronounced responsiveness to BR stimulation. Conclusion Our work explains genome-wide identification, characterization, and expression analysis of gerbera’s BZR transcription factor family. We hinted that these seven GhBEHs are involved in petal growth and development regulation. These findings provide a basis for further studies on the biological function of the BZR gene family in petal growth and a theoretical basis for future horticultural application in gerbera.